Challenges and opportunities in the use of technology for teaching english as a foreign language - Mauliska, Nur; Karlssön, Monica; Djeni, Darwin (Interling : International Journal of English Language Teaching, Literature and Linguistics, 2024)
This study explores the challenges and opportunities in the use of technology for teaching English as a Foreign Language (EFL). Using a qualitative approach with a case study method, data were collected through interviews with teachers, students, and school administrators, as well as classroom observations and document analysis. Key findings indicate that significant challenges include limited access to technology, a lack of technical skills among teachers, and concerns about privacy and data security. However, technology also offers significant opportunities, such as increased student motivation, more adaptive learning, and broader access to educational resources. The findings highlight the need for comprehensive strategies to address these challenges, including better teacher training and the development of technological infrastructure. This study provides valuable insights for designing policies and practices that support the effective integration of technology in EFL teaching, with the hope of improving the quality of education in the digital era.